Analysis of multimode fiber bundles for endoscopic spectral-domain optical coherence tomography - Risi, Matthew D. (Appl Opt, 2015)
A theoretical analysis of the use of a fiber bundle in spectral-domain optical coherence tomography (OCT) systems is presented. The fiber bundle enables a flexible endoscopic design and provides fast, parallelized acquisition of the OCT data. However, the multimode characteristic of the fibers in the fiber bundle affects the depth sensitivity of the imaging system. A description of light interference in a multimode fiber is presented along with numerical simulations and experimental studies to illustrate the theoretical analysis.